1996
DOI: 10.1021/bi960072w
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Complex Crystal Structures of Glycogen Phosphorylase with the Transition State Analogue Nojirimycin Tetrazole and Phosphate in the T and R States,

Abstract: Catalysis by glycogen phosphorylase involves a mechanism in which binding of one substrate tightens the binding of the other substrate to produce a productive ternary enzyme-substrate complex. In this work the molecular basis for this synergism is probed in crystallographic studies on ternary complexes in which the glucosyl component is substituted by the putative transition state analogue nojirimycin tetrazole, a compound which has been established previously as a transition state analogue inhibitor for a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 55 publications
9
82
0
5
Order By: Relevance
“…The interacting phosphates hypothesis was confirmed crystallographically in the analysis of the transition-state intermediate-like GPb-heptulose 2-P complex (McLaughlin et al, 1984;Hajdu et al, 1987;Johnson et al, 1990), which showed a close P-P distance (of phosphorus atoms of phosphate to cofactor 5"phosphate) of 4.8 A. These studies and recent structural studies on the T-and R-state GPb-NJT-phosphate complexes (Mitchell et al, 1996) have definitively established the location of the substrate phosphate at or near the transition state of the reaction and are consistent with the proposed role for the cofactor 5"phosphate as a general acid.…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…The interacting phosphates hypothesis was confirmed crystallographically in the analysis of the transition-state intermediate-like GPb-heptulose 2-P complex (McLaughlin et al, 1984;Hajdu et al, 1987;Johnson et al, 1990), which showed a close P-P distance (of phosphorus atoms of phosphate to cofactor 5"phosphate) of 4.8 A. These studies and recent structural studies on the T-and R-state GPb-NJT-phosphate complexes (Mitchell et al, 1996) have definitively established the location of the substrate phosphate at or near the transition state of the reaction and are consistent with the proposed role for the cofactor 5"phosphate as a general acid.…”
mentioning
confidence: 57%
“…The close proximity of the product phosphate to the cofactor 5"phosphate provides support for a mechanism in which phosphorolysis of heptenitol is catalyzed by general acid attack of the substrate phosphate, promoted by the cofactor 5"phosphate. The recent X-ray work with NJT and phosphate (Mitchell et al, 1996) also show directly that the substrate phosphate binding site is in the correct position for the general acid attack. The proton is donated by the substrate phosphate in a concerted reaction in which it immediately gains a proton from the cofactor 5"phosphate.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations